Культурная среда библиотеки как ресурс поликультурного общества (Библиосфера, 2010)
Basing on the terminological analysis of the notions «cultural environment», «social environment», «library environment» an attempt is made to define the notion «cultural environment in the library». The content of the cultural environment in the library is given and its role as a resource in poly-cultural environment is shown.